Elites and governance in China - Zang, Xiaowei; Kou, Chien-wen (Routledge Studies on China in Transition, 2013)
This book reveals the complex relationship between elite perceptions and behaviour, and governance, in China. It moves away from existing scholarship by focusing on functionaries, grass-roots elites, leading intellectuals, and opinion-makers in China and by looking beyond the top leadership, makes a significant contribution to our understanding of shared governance and broadened political participation in China--Provided by publisher.